Fatores determinantes da adesão ao tratamento fonoterapêutico decrianças com necessidades especiais. - Karine Lara Vivas (2008)
The objective of this study was to investigate the perception of caregivers on the determining factors of compliance to speech and hearing therapy for children with special needs. It is a qualitative descriptive-exploratory study carried out in the AME Clinical School in Belo Horizonte, State of Minas Gerais, Brazil, which provides care for underprivileged children with special needs. The research subjects are 11 family members (10 mothers and 1 father) who provide daily care for their children. Data was collected by a semi-structured interview, focus group, participant field diary, researcher field diary and discourse analysis was used to process the data collected. Seven themes arose with their respective categories: The process of discovering the childs problem after birth, over time, family perception, information from health workers; Reactions in the face of the diagnostic and over time; Surprise/shock, despair/revolt, denial, sadness, acceptance, fear, faith and religiousness; Consequences of diagnostic for the family relationship with child, relationship of couple, relationship with other sons and extended family, family routine; Difficulty with child daily care, treatment; Perceptions on participation in speech and hearing therapy of caring family, of partner, of siblings; Factors hindering continuity of speech and hearing stimulus numerous activities, taking for treatment, interference by outsiders; Factors facilitating continuity of speechand hearing therapy belief in the recovery and support from people, family members and health workers. The results of the study show the importance of the way parents become aware of the childs problem and the consequences of the diagnostic on family organization and the relationship with the child, generating attitudes of exclusive dedication and overprotection; interfering in family relations, strengthening the bond or increasing conflicts of the couple; social isolation of the family, modification of family routine, neglecting other children, physical and emotional overload. The participants reported little family participation in treatment with an overload for the main caregiver, while, at the same time, highlighting the value of family, social and health workers support. Hindrances to treatment mentioned were: difficulty to position the child,uncertainty in carrying out the technique, taking the child to the clinic, especially because of the transport and the accumulation of domestic activities and treatment activities. As facilitating factors, they mentioned the belief in the recovery of the child and family, social and health worker support. The study shows the relevance of emotional involvement and support, not only of the family caregiver, but also of the other members of the family, of the community and health workers, in order to optimizethe stimulation of the child, providing a better speech and hearing development. The adaptation of treatment to the situation of each family and the potential of each family is recommended, establishing a relationship of dialogue between the therapist, family and patient, as well as creating social networks of support and reinforcing those whichalready exist.